Pemetaan Temporal Perubahan Penggunaan Lahan Kelapa Sawit di Kecamatan Babulu, Penajam Paser Utara - Toyibulah, Yoga; Yudiansyah, Yudiansyah (Mulawarman University, 2025)
Babulu District in Penajam Paser Utara Regency, East Kalimantan, is an area with high potential in the development of oil palm plantations. However, the increase in oil palm land area raises the issue of land use change, especially rice field conversion. This study aims to map and analyze changes in oil palm land use from 2015 to 2024 using Landsat 8 OLI/TIRS and Landsat 9 OLI/TIRS satellite imagery. The methods used include image pre-processing, onscreen digitization, supervised multispectral classification, and map overlapping to detect spatial changes. The map accuracy test was carried out by cross-checking the results of image digitization and multispectral classification with 30 sample locations in the field that had been checked for veracity. The results of the study show that the use of oil palm land in Babulu District in 2015 was 14,129.25 ha. The use of oil palm land in Babulu District in 2024 will be 15,817.36 ha. The change in the area of oil palm land use in Babulu District increased by 1688.11 ha in a period of nine years, with a rate of change of 187 ha/year. This change is dominated by the northern area of Babulu District which has a steep topography and is the main location for palm oil expansion, driven by topographic factors, the presence of large companies, and the economic value of palm oil commodities. This study shows the importance of spatial monitoring in sustainable land use management and the need for policies that balance economic growth and productive land conservation.